Poor Fertility, Short Longevity, and Low Abundance in the Soil Seed Bank Limit Volunteer Sugarcane from Seed - Pierre, Johann S.; Perroux, Jai; Whan, Alex; Rae, Anne L.; Bonnett, Graham D. (Frontiers in Bioengineering and Biotechnology, 2015)
The recent development of genetically modified sugarcane, with the aim of commercial production, requires an understanding of the potential risks of increased weediness of sugarcane as a result of spread and persistence of volunteer sugarcane. As sugarcane is propagated vegetatively from pieces of stalk and the seed plays no part in the production cycle the fate of seed in the environment is yet to be studied. In this study sugarcane seed samples, collected in fields over a two year period, were used to determine the overall level of sugarcane fertility, seed dormancy and longevity of seed under field conditions. A survey of the soil seed bank in and around sugarcane fields was used to quantify the presence of sugarcane seeds and to identify and quantify the weeds that would compete with sugarcane seedlings. We demonstrated that under field conditions, sugarcane has low fertility and produces non-dormant seed. The viability of the seeds decayed rapidly (half life between 1.5 and 2.1 months). This means that, in Australia, sugarcane seeds die before they encounter climatic conditions that could allow them to germinate and establish. Finally, the soil seed bank analysis revealed there were very few sugarcane seeds relative to the large number of weed seeds that exert a large competitive effect. In conclusion, low fertility, short persistence and poor ability to compete limit the capacity of sugarcane seed spread and persistence in the environment.